Put yourself in his shoes: embodying the archive in Joe Sacco's The Fixer. Issue 4 (2nd October 2022) - Ancic, Ivana
Abstract: This article interrogates the notion that comics that engage with history do so primarily within the scope of the archive. I argue, instead, that drawing and seeing/reading comics are embodied practices that generate meaning and memory in ways that exceed the discursive logic of the archive. Building on existing scholarship on embodied acts of memory within performance studies, I suggest that comics might better be seen in proximity to what Diana Taylor calls "the repertoire": cultural memory embodied in live gestures, rather than deposited in language. Seen through the lens of the repertoire, a comic such as Joe Sacco's The Fixer (2003) offers new ways to make visible and legible the histories that have been left outside the official archives. By opening up for analysis the body, its staging, and its gestures on the page, the lens of the repertoire makes good use of what archival memory dismisses as the site of traumatic aporia: the unreliable testimony of the perpetrator. Rather than dismissing such material, the methodology of the repertoire transforms it into a repository of cultural meanings, which provide an insight into the collective fantasies and imaginaries on which the nationalist archive tends to stay silent.